Who should pay for the continuity of post-trial health care treatments? - Roberto Iunes; Manuela Villar Uribe; Janet Bonilla Torres; Marina Morgado Garcia; Juliana Alvares-Teodoro; Francisco de Assis Acurcio; Augusto Afonso Guerra Junior (BMC, 2019)
Abstract Background The bioethical debate in the world on who should pay for the continuity of post-trials treatment of patients that have medical indication remains obscure and introduces uncertainties to the patients involved in the trials. The continuity of post-trial treatment was only incorporated in the 2000s by the Helsinki Declaration. The Universal Declaration on Bioethics and Human Rights, published in 2006, points out that post-trial continuity may present a broader scope than just the availability of the investigated medicine. In the latest version of this Declaration, in 2013, it was stated that "prior to the start of the clinical trial, funders, researchers and governments of the countries participating in the research should provide post-trial access for all participants who still require an intervention that was identified as beneficial. This information should also be disclosed to participants during the informed consent process". However, a systematic review on the registration of phase III and IV clinical trials, from the clinical trials website, demonstrated that the understanding of the various guidelines and resolutions is conflicting, generating edges in the post-trial setting. For the health authorities of countries where clinical trials take place, the uncertainties about the continuity of the treatments generate gaps in care and legal proceedings against health systems, which are forced to pay for the treatments, even if they are not included in the list of medicines available to the population. Methods Fifty-one representatives from the health, judicial, legislative, patient and academic organizations of eight countries of Latin American and South Korea took part in a meeting in Chile, in 2017, to discuss the responsibility of the treatment continuation after clinical trials. From a hypothetical case of development of a new drug and its studies of efficacy and safety, the participants, divided in groups, proposed recommendations for the problem and pointed out the pros and cons of adopting each recommendation. The groups were, afterwards, confronted by a simulated jury and, finally, issued a final recommendation for the problem. Then, an analysis was made on the content of the recommendations and the pros and cons in adopting conservative or liberal positions, besides the possible impacts of a restrictive regulation regarding the conduction of clinical trials, pointed out by the groups, before and after the simulated jury. Results The theme was widely discussed and about 12 recommendations were proposed by the participants. The main ones took into account aspects related to patients' rights, economic factors and the development of new technologies, above the position of industry and research institutes, as well as the legislation in force in each country. Conclusion The countries of Latin America and South Korea, currently, do not have laws that address patients' rights, moreover, there is no definition on who should be responsible for post-trial treatments. It is suggested that the World Health Organization issue a resolution recommending that all associated countries determine that the pharmaceutical and medical device industries, or those that sponsored it, should continue to provide treatment to all patients who participated in clinical trials and have medical indication to the continuity.